2015
DOI: 10.1093/ajh/hpu264
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum 25-Hydroxy Vitamin D Levels and Blood Pressure Among Adolescents in Two Resource-Limited Settings in Peru

Abstract: Adolescents deficient in 25OHD demonstrated increased DBP and MAP and a trend toward increased SBP, when compared to nondeficient subjects. 25OHD deficiency early in life was associated with elevated BP metrics, which may predispose risk of hypertension later in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Many observational studies have reported an inverse association between low VitD levels and brachial BP in large samples from the general population [23,24,25], but also among Peruvian adolescents [26], middle-aged individuals [27], people aged >60 years and the elderly [28,29], pregnant women and women aged 20-80 years [30,31]. Similarly, the evidence from medium to large observational studies shows strong and independent inverse associations between serum VitD and cfPWV among diverse study populations [32,33,34,35,36,37,38].…”
Section: Summary Of Observational Data On the Relationship Between Sementioning
confidence: 99%
“…Many observational studies have reported an inverse association between low VitD levels and brachial BP in large samples from the general population [23,24,25], but also among Peruvian adolescents [26], middle-aged individuals [27], people aged >60 years and the elderly [28,29], pregnant women and women aged 20-80 years [30,31]. Similarly, the evidence from medium to large observational studies shows strong and independent inverse associations between serum VitD and cfPWV among diverse study populations [32,33,34,35,36,37,38].…”
Section: Summary Of Observational Data On the Relationship Between Sementioning
confidence: 99%
“…Additionally, a cross-sectional analysis of 1460 participants in Shanghai showed high prevalence of vitamin D deficiency (55.8%) in middle-aged and elderly Chinese men [ 75 ]. In adolescents (aged 13–15), a study of 1441 Peruvians showed an inverse association between vitamin D deficiency and blood pressure, which may predispose risk of HTN later in adulthood [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, diastolic blood pressure was higher in the 25(OH)D 3 -deficient group than the 25(OH)D 3 -sufficient group ( P = 0.04). [ 10 ] Pacifico et al . similarly concluded that with increasing serum 25(OH)D 3 levels, there was a significant decrease in median systolic and diastolic blood pressure values.…”
Section: Itamin D and The H mentioning
confidence: 99%